Bartered bridegrooms : transacting Muslim masculinities as colonial legacy - Bi, Suriyah (Manchester University Press, 2024)
In this eye-opening ethnography, we learn about the experiences of Muslim migrant husbands from Pakistan and Kashmir, who marry their British counterparts in the hope of marital and global social mobility bliss. For many, the parallel and intertwined migration and marital journeys do not pan out in the way they had hoped. Many experience precarity and vulnerability within the household and/or in employment, with some even being subjected to harrowing forms of domestic violence. Migrant husbands navigate an increasingly hostile British immigration system not only in public but also in private, at the hands of their wives and in-laws. The ethnography demonstrates how citizenship can be deployed as a performance of white power within single group identity, differentiated through colonial legacies of 'Britishness'.